Pengaruh Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Pada Sistem Keuangan Desa - Kadek Doni Dananjaya; Gede Juliarsa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
The rapid development in the development of accounting information systems, such as Siskeudes, was initially not integrated online with the local government. However, it was later adapted to be integrated online. The purpose of this study was to determine the influence of human resources and the use of information technology on the village financial system. The population in this study were village heads, village secretaries, village treasurers, IT operators, BPD, LPM, and community leaders in the city of Denpasar who made financial reports, namely 27 villages. The sample collection used was the purposive sampling method. The sample in this study was determined as many as 4 respondents in each of the 27 villages, so that 102 respondents were obtained. The data analysis technique used was Descriptive Statistics analysis, classical assumption tests and multiple regression analysis. The results of the analysis showed that Human resources have a significant positive effect on the village financial system in Denpasar City, having an impact on improving the village financial system in Denpasar City. The second result of the use of information technology has a significant positive effect on the village financial system in Denpasar City. The increasing use of information technology will have an impact on improving the village financial system in Denpasar City. The implications of this study are that the villages in Denpasar City in terms of human resources are expected to be able to improve their human resources by providing technical training to improve skills in preparing financial reports so that village officials can carry out their duties and can rely on appropriate technological knowledge and will improve the village financial system. In terms of the use of information technology, it is expected to maximize the use of existing information technology, and use software that is in accordance with applicable government regulations so that it can facilitate existing work and ultimately maximize the village financial system in Denpasar City.